GAMBARAN PENGGUNAAN BOTOL SUSU PADA USIA 6-24 BULAN DI WILAYAH KERJA PUSKESMAS SUNGAI PIRING TAHUN 2019 - Ramatul Ridha; Sandra Harianis (Jurnal Kesehatan Husada Gemilang, 2020)
Milk bottles are a means where germs and bacteria breed because milk bottles are difficult to clean. The initial survey conducted by researchers where from 8 cases of diarrhea visited the Poli Anak Puskesmas Sungai Piring, 6 of them did the use of milk bottles and how to wash milk bottles that are not true. Where baduta's mother washes a milk bottle does not use a special cleaner washing the bottle, when baduta's mother makes formula, baduta mother does not wash her hands first and the milk bottle uses only one bottle for one day. The purpose of the study was to find out the picture of the use of milk bottles at the age of 6-24 months in the Working Area of Sungai Piring Health Center, Batang Tuaka Subdistrict, Indragiri Hilir Regency in 2019. This research is descriptive quantitative with cross sectional design. Population number 901 children, sampling using accidental sampling with a sample number of 100 baduta children. The research was conducted in the Working Area of Sungai Piring Health Center from July 29 to August 5, 2019. The results of the study obtained as many as 100% who use the type of unseed milk bottle, 85% who have the amount of 1 bottle of milk, 98% can not answer the question correctly (Hygiene), 16% still use the milk bottle after 2 hours. This research is expected for health workers to provide counseling on the importance of maintaining the cleanliness of milk bottles.